Association between CES1 rs2244613 and the pharmacokinetics and safety of dabigatran: Meta-analysis and quantitative trait loci analysis - Li, Haobo; Zhang, Zhu; Weng, Haoyi; Qiu, Yuting; Zubiaur, Pablo; Zhang, Yu; Fan, Guohui; Yang, Peiran; Vuorinen, Anna-Leena; Zuo, Xianbo; Zhai, Zhenguo; Wang, Chen (Frontiers in Cardiovascular Medicine, 2022)
Objective To date, the influence of the carboxylesterase 1 (CES1) rs2244613 genotype on the pharmacokinetics (PKs) and safety of dabigatran remains controversial. Hence, a systematic review was performed to study the association between CES1 rs2244613 genotype and the PKs and safety of dabigatran and CES1 relative expression. Methods In addition to the three English databases (Web of Science, PubMed, and Embase), two Chinese databases (CNKI and Wanfang) were thoroughly revised. The mean differences (MD) and corresponding 95% confidence intervals (CI) were applied to evaluate the differences in PKs between the CES1 rs2244613 genotype. Odds ratio (OR) was used to study the risk for bleeding events between the CES1 rs2244613 genotypes. Subsequent expression quantitative trait loci (eQTL) analyses were performed to evaluate genotype-specific expressions in human tissues. Results Ten studies (n = 2,777) were included. CES1 rs2244613 G allele carriers exhibited significantly lower dabigatran trough concentrations compared to T allele carriers (MD: −8.00 ng/mL; 95% CI: −15.08 to −0.92; p = 0.03). The risk for bleeding events was significantly lower in carriers of the G allele compared to T allele carriers (OR: 0.65; 95% CI: 0.44–0.96; p = 0.03). Subsequent eQTL analysis showed significant genome-wide expressions in two human tissues, whole blood (p = 5.1 × 10–10) and liver (p = 6.2 × 10–43). Conclusion Our meta-analysis indicated a definite relation between the CES1 rs2244613 genotype and tolerability variations or pharmacokinetic fluctuations. The carriers of T allele showed higher dabigatran concentrations; therefore, they would benefit from a dose reduction. Systematic review registration [https://inplasy.com/inplasy-2022-6-0027/], identifier [NPLASY202260027].